A. M. VARYNSKA: TERM FORMATION IN UKRAINIAN MARITIME TERMINOLOGY (STRUCTURAL AND FUNCTIONAL CHARACTERISTICS) - VARYNSKA, A. M. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. The formation of Ukraine as an independent state is associated with the sea and the maritime industry, and therefore the study of the maritime terminology system, its compliance with international terminological norms, acquires state significance. In this regard, the problem of a deep and comprehensive study of the term system of the maritime industry is not only an urgent and demanded scientific direction, but also a necessary condition for its development. Purpose. Substantiate certain processes of terminology of verbal and non-verbal parameters in Ukrainian maritime terminology. Methods. In order to comprehensively study the Ukrainian maritime terminology used: 1) the method of continuous sampling; 2) the method of component analysis, which is aimed at improving and refining vocabulary definitions of marine terms; 3) structural method, in combination with distributive analysis (used to define and describe the semantic structure of marine terms); 4) the method of word-formation analysis (used to establish the mechanism of word formation and its place in the vocabulary of the language); 5) structural-morphological approach (used to clarify the structure of derivative terms and to determine the basic models of term formation); 6) modeling method (used to determine the term formation of various structural models); 7) comparative method, which is based on the identification of common and distinctive features of verbal and nonverbal dimensions in the term formation of Ukrainian maritime terminology; 8) comparative-historical method, which is based on the history of the Ukrainian language and the development and formation of Ukrainian maritime terminology, determines the linguistic and cultural specifics of its formation; 9) general scientific methods are also used: observation, generalization, classification. Results. The study analyzes the functioning of the Ukrainian maritime terminology in terms of origin and use; the semantic meaning of the terms is highlighted; the semantic method of terminology is considered, in particular, the semantic transformations of metaphor and metonymy, as well as the processes of terminology, reterminology and determinology; the importance of the morphemic way of forming the term is noted; highlighted the structural features of the formation of one-component and multicomponent terms; substantiates the meaning of abbreviated processes in the functioning of terms; the terminological components of verbal and non-verbal components in the Ukrainian maritime terminology are considered. Originality. The novelty of the study is that for the first time the processes of creation of Ukrainian maritime terms are characterized at the structural and functional level; their verbal and nonverbal dimensions are thoroughly considered. Conclusion. Ukrainian maritime terminology is an integral part of the Ukrainian lexical system, and it is characterized by the same processes that occur in the literary language: some terms go out of use, new ones appear, some are radically changed, rethought. The maritime industry in Ukraine is constantly and dynamically developing, a large number of new maritime terms appear. Understanding the processes of formation of terms in Ukrainian maritime terminology is an indicator of the socio-economic, cultural and scientific development of society and indicates a high level of its development, its mobility and consistency.